ANALISIS KINERJA KEUANGAN PERUSAHAAN DENGAN MENGGUNAKAN METODE ECONOMIC VALUE ADDED (EVA) DAN MARKET VALUE ADDED (MVA) PADA PERUSAHAAN OTOMOTIF DAN KOMPONEN YANG TERDAFTAR DI BEI TAHUN 2013-2015 - Kusuma, Maulana Hadi (Program Studi Manajemen Fakultas Ekonomi Universitas Palembang, 2019)
Analysis of Economic Value Added (EVA) and Market Value Added (MVA) analysis on automotive and component companies at BEI, from 2013-2015. This study aims to measure the company's financial performance using Economic Value Added (EVA) and Market Value Added (MVA) methods. The object of this research is at automotive company and component at BEI year 2013-2015. The data collection techniques through documentation. EVA research results: If EVA value> 0 or EVA is positive then operating profit after tax exceeds the cost of capital needed to generate the profit. This means the company's management has succeeded in creating economic value-added for the company. And if the EVA <0 or EVA value is negative then the operating profit after tax is less than the cost of capital needed to generate the profit. This means there is no process of adding economic value to the company. The researcher concludes that the analysis of Economic Value Added (EVA) of the three companies in automotive sub sector and EVA's negative.